Computational simulations of perovskite solar cell technologies under varying operation conditions - Kamppinen, Aleksi (fi=Turun yliopisto|en=University of Turku|, 2026)
Perovskite solar cells are promising for photovoltaic light conversion to electricity with a high power conversion effciency. The key materials, perovskites, are a large group of materials, and their properties can be tuned by altering the composition, which makes perovskites adaptable to different applications. Perovskites may be applied in single- or multi-junction cells and in different environments, such as varying outdoor conditions or indoors. The high performance in different applications and tunability of perovskites has also inspired development of other materials, which resemble perovskites. These perovskite-inspired materials further expand the material design and application alternatives. As the perovskite technologies move closer to the commercial applications, it is important to understand the interconnected effects of material properties and varying operation conditions. This thesis studies perovskite and perovskite-inspired material absorbers in photovoltaic applications in different operation conditions, including indoor lighting and varying outdoor weather conditions. Optical, electrical, and thermal models are applied to computationally simulate the devices and the conditions. First, optical characterization and modelling are conducted to understand the optical limits for the photogeneration and radiative limit effciency of two emerging lead-free perovskite-inspired materials under artifcial indoor lighting. The results reveal a large margin between the optical limits and the experimental state of the art, which is hoped to improve in the future, for example, with insights from optoelectronic modelling enabled by the produced optical constant data. Second, parasitic heat generation and operation temperature of perovskite solar cells and panels in realistic outdoor conditions are predicted. The band gap dependence of parasitic heat generation in planar PSCs is quantifed and a perovskite panel is predicted to operate in ca. 7 ∘C lower temperature than a comparable silicon panel in reference conditions, for example. Finally, the correlated effects of layer thicknesses are analysed for structure optimization, a topic which follows throughout the thesis. In the future, the applied methods and obtained results may enable the development of perovskite-based photovoltaics for the application specifc conditions.